REGULATION, EXPOSURE, RECOGNITION (RER) THEORY FOR IMPROVED ESL TEACHING EXPERIENCE IN CEBU - Dr. Jennifer B. Gonzales (International Journal of Research Science and Management, 2018)
The demand for ESL teachers in Cebu has been increasing from 2004 to present, which boosted Cebu’s economy in terms of job opportunities and tourism. This paper explored the lived experiences of the ESL teachers in Cebu, revealing their challenges and opportunities to generate a theory. This study used qualitative Husserlian Phenomenological research design, using Collaizi’s qualitative analysis method, as well as inductive theory development approach. The participants were ESL teachers purposively and conveniently selected. The teachers’ challenges includeissues on social stratification, salary, employment regularization, cultural difference and communication, and teaching competence. The opportunities include improved English communication, exposure to international culture, and local and international opportunities. From the result and themes extracted, RER Theory for Improved ESL teaching Experience in Cebu is generated. It is concluded that regulation of ESL schools in Cebu improves the ESL teachers’ social status, competence and experiences and creates local and international economic advantage. It is recommended that regulation government regulation and interagency support on ESL teachers be granted. It is further recommended that HEIs maximize the training of communication and teaching competencies of their graduates to retain quality ESL teachers and capitalize ESL economic potential.